Joan's family bill of rights: an essay by Barbara Lewis. (17th October 2014) - Lewis, Barbara
Abstract : After spending two weeks in an intensive care unit watching her sister, Barbara Lewis was spurred to improve interactions with hospital staff by writing a bill of rights for families and carers and championing the development of patient and family advisory councils in US hospitals